Glutaminase 1 Regulates Neuroinflammation After Cerebral Ischemia Through Enhancing Microglial Activation and Pro-Inflammatory Exosome Release - Gao, Ge; Li, Congcong; Zhu, Jie; Wang, Yi; Huang, Yunlong; Zhao, Shu; Sheng, Shiyang; Song, Yu; Ji, Chenhui; Li, Chunhong; Yang, Xiaoyu; Ye, Ling; et al. (Frontiers in Immunology, 2020)
Cerebral ischemia induces a robust neuroinflammatory response that is largely mediated by the activation of CNS resident microglia. Activated microglia produce pro-inflammatory molecules to cause neuronal damage. Identifying regulators of microglial activation bears great potential in discovering promising candidates for neuroprotection post cerebral ischemia. Previous studies demonstrate abnormal elevation of glutaminase 1 (GLS1) in microglia in chronic CNS disorders including Alzheimer’s disease and HIV-associated neurocognitive disorders. Ectopic expression of GLS1 induced microglia polarization into pro-inflammatory phenotype and exosome release in vitro. However, whether GLS1 is involved in neuroinflammation in acute brain injury remains unknown. Here, we observed activation of microglia, elevation of GLS1 expression, and accumulation of pro-inflammatory exosomes in rat brains 72 h post focal cerebral ischemia. Treatment with CB839, a glutaminase inhibitor, reversed ischemia-induced microglial activation, inflammatory response, and exosome release. Furthermore, we found that the application of exosome secretion inhibitor, GW4869, displayed similar anti-inflammatory effects to that of CB839, suggesting GLS1-mediated exosome release may play an important role in the formation of neuroinflammatory microenvironment. Therefore, GLS1 may serve as a key mediator and promising target of neuroinflammatory response in cerebral ischemia.